EFEK IKLAN SELEBGRAM SEMARAS SIA DALAM MENINGKATKAN MINAT KONSUMEN MELAKUKAN PEMBELIAN ONLINE PRODUK UMKM - Kurniawansyah, K; Fitriyani, Ika; Arisky, Ragil (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
This study aims to know the effect of Semaras Sia selegram advertisements on consumer interest in purchasing online of MSME products. The type of this study was associative which aims to examine the effect of Semaras Sia selegram advertisements (X) on consumer interest in purchasing online of MSME products (Y). The type of data used was quantitative data collected directly by researchers from research respondents using a research instrument in the form of a questionnaire. The sample used in this study were netizens who liked advertising posts from Semaras Sia selegram, totaling 95 people and selected using non-probability sampling techniques with convenience sampling or accidental sampling methods. The data analysis tools used simple linear regression analysis techniques, t test, and the coefficient of determination (R2) test. Based on the results of the hypothesis test, it showed that the calculated t value was 3.748, which was greater than the t table value of 1.986 (3.748?1.986) and the resulting probability value was 0.000, which was less than 0.05 (0.000?0.05), so it can be stated that Semaras Sia selegram advertisements had a positive and significant effect on consumer interest in purchasing online of MSME products. The ability of Semaras Sia selegram advertisements in explaining the variation of changes on consumer interest in purchasing online of MSME products was 13.1%, while the remaining of 86.9% was affected by other variables outside this research model, such as information quality, information value, media display, price, and trust.